Facile hydrothermal synthesis of antibacterial multi-layered hydroxyapatite nanostructures with superior flexibility. Issue 9 (13th February 2018) - Qi, Mei-li; Huang, Zhennan; Phakatkar, Abhijit; Yao, Wentao; Yuan, Yifei; Foroozan, Tara; Xiao, Gui-yong; Shahbazian-Yassar, Reza; Lu, Yu-peng; Shokuhfar, Tolou
Abstract : The synthesis of silver-doped multi-layered hydroxyapatite nanobelts is of great importance due to their being a potential candidate to curb the infections associated with HA implants along with their advantage as a reinforcement in biomaterials. Abstract : The synthesis of silver-doped hydroxyapatite (Ag-HA) nanobelts as a HA-based antibacterial bioactive material is of great importance due to their being a potential candidate to curb the infections associated with HA implants along with their advantage as a reinforcement in biomaterials. Here, a facile one-step method for synthesizing Ag-doped hydroxyapatite (Ag x HA) [Ca10− x Ag x (PO4 )6 (OH)2 ] ( x = 0, 0.2, 0.5) nanobelts using hydrothermal homogeneous precipitation is demonstrated. The samples were characterized using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy (EDS). Their antibacterial properties against Escherichia coli ( E. coli ) bacteria and cytotoxicity to Swiss embryonic mouse fibroblast (3T3-J2) cells were evaluated with the help of the disc diffusion method and MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide) cell viability assay, respectively. Our study indicates that the increased optimum Ag amount in the HA nanobelt has enhanced its antibacterial properties and bioactivity. The flexibility behavior of an individual multi-layered Ag0.2 HA nanobelt was observed by in situ TEM. The novel TEM cyclic compression–bending test results indicate that the Ag0.2 HA nanobelt can retain its original shape after eight continuous deformation cycles at an extreme angle, revealing its high flexibility. This study provides new insights into the design of bioactive HA nanobelts with antibacterial properties and opens new opportunities for their load-bearing applications.